Determination of Sea Ice Surface Roughness from Laser Altimeter Waveform - Csatho, Beata M.; Thomas, Robert H. (Byrd Polar Research Center, The Ohio State University., 1995)
One of the Geoscience Laser Altimeter System (GLAS) level 2 products is the surface roughness. Our objective is to develop an algorithm for the determination of sea ice surface roughness from altimeter waveforms. The purpose of this report is to provide a summary of the work performed and problems encountered until now. Based on the knowledge of the sea ice properties (reflectance, surface roughness) a set of sea ice models is created. Laser waveforms are computed using the GLAS Laser Altimetry Simulator software. Then the surface roughness is estimated from the waveform. By comparing the actual and estimated surface roughnesses, different surface-roughness algorithms can be evaluated. For horizontal, random rough surfaces with Lambertian reflectance, the RMS surface roughness - defined as the standard deviation of elevations within the foot print - can be estimated from the mean-square width of the received pulse. For more general surfaces, we can define the equivalent horizontal, Lambertian, random rough surface that produces the same RMS laser pulse width. Future work will include an assessment of whether information on non-random roughness can be extracted from the pulse shape.